Kesenjangan Hasil Belajar Matematika Ditinjau dari Pembelajaran Kooperatif, Kemampuan Bahasa dan IPA - H. Faad Maonde (Jurusan Pendidikan Matematika FKIP Universitas Halu Oleo,, 2014)
The experiment research with 3x3 factorial design had aim to assess the discrepancy of mathematics learning outcomes in terms of models of cooperative learning, Indonesian language ability, English and natural science in 2012/2013 at Kendari. The results of the analysis used EViews program that involved 540 students at nine elementary Schools had discovered: (i) STAD and Jigsaw learning model are more effective than TSTS type, (ii) in any learning is needed character education, and (iii) the gap of -1, 2,3,4 type mathematics learning outcomes accept the null hypothesis (H0) which means that the set of learning by LP-01evaluation in RPP character increase relatively the low understanding group of students equall to the smart group of students. Keywords: Discrepancy, mathematics learning outcomes, STAD, Jigsaw, TSTS cooperative, language and natural science ability